ENERGETICS OF WATER MOLECULE ADSORPTION ON MODIFIED BENTONITE SURFACES - Mamajonova, Moxfora; Salixanova, Dilnoza; Abduraxmonov, Eldor; Ismailova, Muxtasar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In this study, the energetics of adsorption of water molecules on modified (enriched and activated) Dehkanabad bentonite were studied in depth. Based on experimental data, adsorption isotherms and differential heats of adsorption (Qd) were determined, and molar differential entropy (ΔSd) values were calculated using the Gibbs–Helmholtz equation. The results of the study showed that water molecules adsorbed on the surface of modified bentonite in a stepwise manner, and the values of adsorption heat and entropy changed depending on the degree of surface filling. In the initial stages, high-energy adsorption centers were active and characterized by high heat ( 71.7 kJ/mol), while in the later stages, the heat decreased and manifested itself in the form of plateaus. Entropy analysis revealed that the mobility and disorder of water molecules in the surface phase were sometimes higher than that of liquid water. Kinetic observations showed that the time to reach adsorption equilibrium depends on the degree of surface coverage and the redistribution of structural cations. The results of this work provide an important scientific basis for assessing the efficiency of modified bentonite-based sorbents in absorbing water vapor and determining the directions of their practical application.